Forage Production Characteristics of Japanese Papaya (Cnidoscolus aconitifolius) as Ruminant Feed - Husnassabil, Ahmad Hadin; Marjuki, Marjuki; Susilorini, Tri Eko; Kuswati, Kuswati; Surjowadojo, Puguh; Nurul Huda, Asri; Putri, Aprillia Ika; Gani, Tifany Sonia (CV. Komunitas Dunia Peternakan, 2025)
This study aimed to evaluate the forage production characteristics of Japanese papaya (Cnidoscolus aconitifolius) as a potential feed source for ruminant livestock. The research employed a case study approach through direct field observations on four mature Japanese papaya plants naturally grown as living fences in Malang City. Measured variables included the diameter of the main branch, number and length of sub-branches, forage yield, and nutrient composition. Data were analyzed using correlation and simple linear regression to determine the relationship between plant structure and forage productivity. The results indicated that the diameter of the main branch showed a strong positive correlation with the number and length of sub-branches, as well as with forage yield and nutrient content (DM, OM, CP, CF, and EE). Regression analysis confirmed that larger branch diameters were consistently associated with higher forage production and better nutrient values. These findings suggest that the diameter of the main branch can serve as a reliable indicator for estimating the forage yield and nutritional potential of Japanese papaya, providing a practical tool for its use in sustainable ruminant feed management.